MicroRNA828 negatively regulates lignin biosynthesis in stem of Populus tomentosa through MYB targets. (26th February 2022) - Wang, Xianqiang; Yao, Shu; Htet, Win Pa Pa Myo; Yue, Yuchen; Zhang, Zhuanzhuan; Sun, Kuan; Chen, Sijie; Luo, Keming; Fan, Di
Abstract: Lignin biosynthesis in the sclerenchyma cells is strictly controlled by a complex network of genetic and environmental signals. In the last decades, the transcriptional regulation of lignin synthesis in woody species has been established. However, the role of microRNA-mediated post-transcriptional modulation in secondary cell wall biosynthesis remains poorly understood. Here, we identified a microRNA, miR828, involved in the regulation specific to lignin biosynthesis during stem development in Populus tomentosa Carr . miR828 is preferentially expressed in the secondary vascular tissues during stem development. Two MYB genes ( MYB171 and MYB011 ) were validated as direct targets of miR828 by degradome analysis and green fluorescent protein signal detection. Overexpression of miR828 in poplar downregulated genes for lignin biosynthesis, resulting in reduced lignin content in cell walls. Conversely, suppression of miR828 in plants by the short tandem target mimics elevated the expression of lignin biosynthetic genes and increased lignin deposition. We further revealed that poplar MYB171, as the most abundant miR828 target in the stem, is a positive regulator for lignin biosynthesis. Transient expression assays showed that both MYB171 and MYB011 activated PAL1 and CCR2 transcription, whereas the introduction of miR828 significantly suppressed their expression that was induced by MYB171 or MYB011. Collectively, our results demonstrate that the miR828-MYBs module precisely regulates lignin biosynthesis during the stem development in P. tomentosa through transcriptional and post-transcriptional manners.